Mollusk diversity in the intertidal zone of Menganti Beach, Kebumen, Central Java - Steviana Amalia Ratih; Meilisha Putri Pertiwi; Raden Teti Rostikawati (Depik, 2021)
Limited information about Mollusks in Menganti Beach, Central Java has been a strong basis for researching its diversity. This study aimed to determine the mollusks' diversity in Menganti Beach, Kebumen. The research was conducted from April to May 2020, using a survey method and purposive sampling technique. Sampling was undertaken at three stations with the belt transect method. The results revealed 37 species with 1767 individuals from the Class Bivalvia, Gastropods, and Polyplacophora. Based on the diversity index value H '= 3.3, station 1 with the rocky sand substrate is the best for mollusks' habitat. The H' value at station 1 shows the highest diversity that the base substrate is dominated by sand and rocks, which are very supportive of mollusks. It is supported by the evenness value (E), which indicates evenly distributed species, and dominance value (D), which does not indicate a species' dominance. The a-biotic parameters at the three stations obtained an average morning temperature of 29 oC and 30 oC in the afternoon, pH of 7, and a salinity of 30 so that these values support the Mollusk habitat at Menganti Beach, Kebumen.Keywords:MolluskDiversityIntertidal ZonesCoastal